Complete mitogenomes and phylogenetic relationships of Haemaphysalis nepalensis and Haemaphysalis yeni - Lu, Xin-yan; Zhang, Quan-fu; Jiang, Dan-dan; Liu, Ya-fang; Chen, Bin; Yang, Shuang-ping; Shao, Zong-ti; Jiang, Hang; Wang, Jian; Fang, Yi-hao; Du, Chun-hong; Yang, Xing (Frontiers in Veterinary Science, 2022)
The mitochondrial genome may include crucial data for understanding phylogenetic and molecular evolution. We sequenced the complete mitogenome of Haemaphysalis nepalensis and Haemaphysalis yeni for the first time. H. nepalensis and H. yeni's complete mitogenomes were 14,720 bp and 14,895 bp in size, respectively, and both contained two ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and 13 protein-coding genes (PCG). Haemaphysalis nepalensis have one control region (D-loop). The adenine + thymine concentration of the genomes of H. nepalensis and H. yeni was 77.75% and 78.41%, respectively. The codon use pattern and amino acid content of proteins were both observed to be affected by the AT bias. Genes in the mitogenome were organized and located in a comparable manner to previously known genes from Haemaphysalis ticks. Mitochondrial PCGs were used to perform phylogenetic relationships based on the Minimum Evolution (ME) approach using MEGA 7.0 software, the results reveal that H. nepalensis has tight links with H. tibetensis, H. yeni and H. kolonini share a sister group relationship and that H. nepalensis and H. yeni belong to Haemaphysalis. The results of this study include the following: i) discovered and supplied new tick records (H. nepalensis) for China, ii) provided the first complete mitochondrial genome for H. nepalensis and H. yeni and revealed their phylogenetic relationships, and iii) the features of the mitochondrial genome of H. nepalensis and H. yeni provided more genetic reference for phylogeography, systematics, and population genetics of the Haemaphysalis species.